mtDNA Heteroplasmy at the Core of Aging-Associated Heart Failure. An Integrative View of OXPHOS and Mitochondrial Life Cycle in Cardiac Mitochondrial Physiology - Elorza, Alvaro A.; Soffia, Juan Pablo (Frontiers in Cell and Developmental Biology, 2021)
The most common aging-associated diseases are cardiovascular diseases which affect 40% of elderly people. Elderly people are prone to suffer aging-associated diseases which are not only related to health and medical cost but also to labor, household productivity and mortality cost. Aging is becoming a world problem and it is estimated that 21.8% of global population will be older than 65 years old in 2050; and for the first time in human history, there will be more elderly people than children. It is well accepted that the origin of aging-associated cardiovascular diseases is mitochondrial dysfunction. Mitochondria have their own genome (mtDNA) that is circular, double-stranded, and 16,569 bp long in humans. There are between 500 to 6000 mtDNA copies per cell which are tissue-specific. As a by-product of ATP production, reactive oxygen species (ROS) are generated which damage proteins, lipids, and mtDNA. ROS-mutated mtDNA co-existing with wild type mtDNA is called mtDNA heteroplasmy. The progressive increase in mtDNA heteroplasmy causes progressive mitochondrial dysfunction leading to a loss in their bioenergetic capacity, disruption in the balance of mitochondrial fusion and fission events (mitochondrial dynamics, MtDy) and decreased mitophagy. This failure in mitochondrial physiology leads to the accumulation of depolarized and ROS-generating mitochondria. Thus, besides attenuated ATP production, dysfunctional mitochondria interfere with proper cellular metabolism and signaling pathways in cardiac cells, contributing to the development of aging-associated cardiovascular diseases. In this context, there is a growing interest to enhance mitochondrial function by decreasing mtDNA heteroplasmy. Reduction in mtDNA heteroplasmy is associated with increased mitophagy, proper MtDy balance and mitochondrial biogenesis; and those processes can delay the onset or progression of cardiovascular diseases. This has led to the development of mitochondrial therapies based on the application of nutritional, pharmacological and genetic treatments. Those seeking to have a positive impact on mtDNA integrity, mitochondrial biogenesis, dynamics and mitophagy in old and sick hearts. This review covers the current knowledge of mitochondrial physiopathology in aging, how disruption of OXPHOS or mitochondrial life cycle alter mtDNA and cardiac cell function; and novel mitochondrial therapies to protect and rescue our heart from cardiovascular diseases.